Factorize completely x^3 - 6x^2 + 11x - 6

Let f(x) = x^3 - 6x^2 + 11x - 6.

Try x = 1:   f(1) = 1 - 6 + 11 - 6 = 0

So x - 1 is a factot of f(x).

Try x = 2:   f(2) = 8 - 24 + 22 - 6 = 0

So x - 2 is a factot of f(x).

Try x = 3:  f(3) = 27 - 54 + 33 - 6 = 0

So x - 3 is a factot of f(x).

Thus         x^3 - 6x^2 + 11x - 6 = (x - 1)(x - 2)(x - 3)

Answered by Kai W. Maths tutor

20903 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

(GCSE) A rectangle has the following characteristics: its length is (2x + 5), its width is (3x - 2). The perimeter of the rectangle is 46 cm. What is the value of x?


Write cosx - 3sinx in the form Rcos(x + a)


Find the derivative of x^3 - (y^2)x =3


I don't understand chain rule for differentiation especially when combined with more complex functions.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences